Effects of Profitability Leverage & Liquidity on Risk Management Disclosure - Komara, Acep; Riana, Nais (Jurnal Ekuisci, 2024)
This study aims to analyze the effect of Profitability, Leverage, and liquidity on Risk Management Disclosure with the object of research, namely property and real estate companies listed on the Indonesia Stock Exchange for the 2019-2022 period. This primary research uses secondary data in the form of annual financial statements. The population in this study is 73 property and real estate companies listed on the IDX for the 2019-2022 period. Sampling in this study used purposive sampling and obtained research samples of 9 companies with a research period of 4 years of observation into 36 samples. The data analysis technique in this study uses IBM SPSS 26 with statistical analysis of the Classical Assumption Test, Multiple Linear Regression Test, and Coefficient of Determination. The results of this study show that Profitability does not affect risk management disclosure, while leverage and liquidity affect risk management disclosure.